Integrating Eco-efficiency in rail vehicle design - Dewulf, Wim (Leuven University Press, 2001)
The total amount of transport is growing fast in the global economy and one unavoidable effect of this is the adverse environmental impact. An eco-efficient transport system is therefore a prerequisite for the development towards a sustainable society. Railways and the train industry have an important role to play in this context and one of the core components here is the rolling stock. The developments of eco-efficient trains and train components is a complex task, requiring an immense amount of information and effective support tools. Addressing these issues is the aim of the RAVEL methodolgy and the underlying theme of this book. This book offers the reader: a summary of the needs for Design for Environment (DfE) and the requirements for a rail qvehicle specific DfE system; a presentation of the Ravel methodology developed to cope with the specific needs of the rail sector. The methodology includes a practical and quantifiable definition of eco-efficiency, based on environmental performance indicators. Supporting components of the methodology include standardised data formats, a predefined material list and a knowledge system; a description on how the methodology has been implemented in an information system and as a web-based prototype software. The book is the final report of the RAVEL project (RAil VEhicLe eco-efficient design), co-financed by the European Commission under the Industrial and Material Technologies Programme. The project was carried out between November 1998 and October 2001 by a team from Bombardier Transportation (co-ordinator), ABB Corporate Research, Chalmers University of Technology, The Danish Railways (DSB), Gesellschaft f